A Comparative Analysis of Environmental Management System Implementation in Fertilizer Industries: Case Study of PT Pupuk Kaltim, PT Pupuk Kujang, and PT Petrokimia Gresik - Fahri Fardiansyah; Filson Maratur Sidjabat (Fakultas Teknik, 2021)
Considering Indonesia as an agricultural country, it certainly needs a support to have an adequate supply of fertilizer. Currently, the development of the fertilizer industry in Indonesia is quite rapid. Due to a large demand of fertilizers, the fertilizer industry is trying to provide good quality products to ensure customer’s satisfaction. In addition to improving product quality, fertilizer producers in Indonesia also strive to environmental management system aspects as an effort to implement ISO 14001:2015. The objective of this study is to analyze the comparison of environmental management system implementation among fertilizer producers in Indonesia, namely PT Pupuk Kaltim, PT Pupuk Kujang, and PT Petrokimia Gresik. The three fertilizer producers were chosen since they had already received ISO 14001: 2015 certification. The method used in this study is a qualitative method by analyzing and interpreting the data that has been obtained. The results show that the implementation strategies in environmental management carried out by the three fertilizer producers are not much different, almost all of them have the same strategy in terms of environmental management. However, PT Pupuk Kaltim has superiority in environmental management compared to its competitors, it is proven by the achievement of the PROPER gold at three consecutive years, while PT Pupuk Kujang and PT Petrokimia Gresik merely achieved the PROPER green category.